2017
DOI: 10.1111/irv.12468
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and ecological risk factors for human influenza A virus infections in rural Indonesia

Abstract: BackgroundIndonesia has the world's highest reported mortality for human infections with highly pathogenic avian influenza (HPAI) A(H5N1) virus. Indonesia is an agriculturally driven country where human‐animal mixing is common and provides a unique environment for zoonotic influenza A virus transmission.ObjectivesTo identify potential demographic and ecological risk factors for human infection with seasonal influenza A viruses in rural Indonesia, a population‐based study was conducted in Cileunyi and Soreang s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The ownership of rabbits, however, was found to be low (1.2% of households). A previous study of ours—also from rural West Java, Indonesia—also found poultry to be a risk factor for development of H3N2 influenza [ 29 ]. Household ownership of livestock such as rabbits and chickens likely leads to exposure to organic dust early in life due to the population’s proximal living with their animals.…”
Section: Discussionmentioning
confidence: 67%
“…The ownership of rabbits, however, was found to be low (1.2% of households). A previous study of ours—also from rural West Java, Indonesia—also found poultry to be a risk factor for development of H3N2 influenza [ 29 ]. Household ownership of livestock such as rabbits and chickens likely leads to exposure to organic dust early in life due to the population’s proximal living with their animals.…”
Section: Discussionmentioning
confidence: 67%
“…Health-care personnel are at increased risk of exposure to IAV as was shown during the 2009 A/H1N1 pandemic (Lietz et al 2016). Individuals who work in close contact with animals, such as birds and swine, may also have an increased risk of zoonotic transmission (Harris et al 2017;Root et al 2017). Although rare, the zoonotic emergence of novel IAV strains has resulted in some of the most widespread influenza virus outbreaks in history (Webster and Laver 1972;Taubenberger and Kash 2010).…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Children younger than 5 are at increased risk of infection, likely because of immature immune development, discussed in detail below. As a result, healthy adults that work with children, such as day-care providers or early educators, or those who have young children at home are >1.5 times more likely to come into contact with influenza viruses (Root et al 2017;Huang et al 2019). A final consideration for increased susceptibility to IAV infection is population density.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Wang et al 7 studied vaccination campaigns in Taiwan and concluded that 3 times the cost of vaccination is generated in savings. The potential for cost savings within tropical areas in which influenza infections occur year-round, such as Singapore 8 and Indonesia, 9 needs to be studied to assess whether vaccination is cost-effective in the absence of clear influenza seasons.…”
Section: Introductionmentioning
confidence: 99%